(untitled) (Weinheim, 2004)
An introduction to the science of nanoparticles, from fundamental principles to their use in novel applications. As a basis for understanding nanoparticle behavior, the book first outlines the principles of quantum size behavior, nanoparticles architecture, formation of semiconductor and metal nanoparticles. It then goes on to describe the chemical syntheses of nanoparticles with defined characteristics, their structural, electrical and magnetic properties, as well as current methods to monitor these properties.
Vật liệu cấu trúc nano
Keywords: Nanoscience,Nanostructures,Khoa học nano